FORMULATION DEVELOPMENT OF ORAL FAST-DISSOLVING FILMS OF RUPATADINE FUMARATE - ROY, ABHIBRATA; AREES, REEGAN; BLR, MADHAVI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Rupatadine fumarate (RF) is an anti-allergic drug indicated for the treatment of allergic rhinitis. It has low oral bioavailability due to its poor aqueous solubility and extensive hepatic first pass metabolism. In the present work, oral fast-dissolving films (OFDF) have been formulated and evaluated to facilitate dissolution in the oral cavity itself. Methods: Pullulan and HPMC (5, 15 cps) were employed as film formers and six formulations were tried. The physicochemical compatibility between drug and the polymers was studied by FTIR spectroscopy. RF-beta-cyclodextrin (BCD) inclusion complex was initially prepared and evaluated. The inclusion complex was incorporated into the film. OFDF were formulated and prepared by solvent casting method. The film size for one dose was 2 × 2 cm. The films were evaluated for various film parameters including disintegration time and drug release. Results: Preliminary film studies indicated % of film former solution to be between 3 and 5% for good appearance, mechanical strength, and quick disintegration. Solubility enhancement of RF is almost 40-fold from its BCD inclusion complex. Drug content in the films ranged between 83 and 90%. The pH ranged between 6 and 7 for all the formulations. All OFDF of RF disintegrated within one minute. With higher viscosity grade of HPMC, disintegration was comparatively slower and so was the drug release. Pullulan based films also showed desirable properties. F3 had disintegration time was 28 s and % drug release was 92% in 180 s. Conclusion: OFDF of RF could be formulated employing pullulan and HPMC low viscosity grades by solvent casting method. F3 containing HPMC E5 at 37% by weight of dry film showed desirable film properties. Stability studies indicated that there was no significant change in the films with respect to physicochemical properties and in vitro release.